Variação denominativa nas modalidades oral e escrita: o léxico da culinária na internet - Odorissio, Renata Maria (Universidade Federal de São Carlos, 2018)
This research aims to analyse the culinary language based on the concept of denominative variation that is applied on several studies theoretically developed under the Communicative Theory of Terminology (CABRÉ, 1999). Our scientific framework is conceived of 280 websites in which recipes and the videos that demonstrate how to prepare them are inserted, which define a very specific content for the research. The text extracted from the recipes was compilated to form a specific corpus (CR) and all the videos were transcribed and compilated in a corpus of transcription (CT). The general hypothesis claims that the denominative variation between the two modalities is small (from 10 to 20%) due to the specificities of our research object and the methods applied to the selection of the lexical units that must be colected from the corpora. This expectation goes against the perception that the degree of specialisation determines the level of variation in a language, so the less specialised is the domaine, the more is the level of denominative variation. The 40th most frequent simple lexical units (SLU) were listed in order to search for compound lexical units (CLU) in the corpora, using a software called Unitex. The analysis also take into consideration the context of usage of the lexical units, through which them we can verify some special aspects associated to the functional factors that affect the units and even concerning the textual composition, in the case of the written texts of the recipes. We extracted 390 ULC and from which 66% are found in both of the corpora (oral and written modalities); 18% are exclusively CR (written modality corpus) and 16% are found only in CT (oral corpus). Even though we have extrated only 22 cases of variants, the general results and linguistic data that are observed show that the variation is more representative than expected, with relevant rates of exclusive variations to one modality. This confirms the relation between a low rate of specificity of the language and its potential of lexical variation.
Denominative Variation in the oral and written modalities: the lexicon of the culinary in the internet
Keywords: Variação denominativa; Modalidade escrita; Modalidade oral; Linguagem culinária; Internet; Denominative variation; Written modality; Oral modality; Culinary language; Internet; LINGUISTICA, LETRAS E ARTES::LINGUISTICA